Lung Cancer in the Very Young: Treatment and Survival in the National Cancer Data Base. Issue 7 (July 2016) - Arnold, Brian N.; Thomas, Daniel C.; Rosen, Joshua E.; Salazar, Michelle C.; Blasberg, Justin D.; Boffa, Daniel J.; Detterbeck, Frank C.; Kim, Anthony W.
ABSTRACT : Introduction: : Young patients with lung cancer represent a distinct subset of patients with this disease. The National Cancer Data Base includes patients of all ages and contains detailed staging, treatment, and survival information. The objective of this study was to examine treatment patterns and outcomes in young patients with non–small cell lung cancer (NSCLC). Methods: : The National Cancer Data Base was queried for NSCLC cases from 2003 to 2009. Younger patients were defined as those aged 20 to 46 years. Older patients were defined as those aged 47 to 89 years. Patient demographics, tumor characteristics, treatment, and survival were analyzed. The primary outcomes were 5‐year overall and relative survival. Results: : The study included 173, 856 patients; 5657 were 20 to 46 years of age. Younger patients were treated differently and received more aggressive therapy at each stage. At stage I, 64% of younger patients received surgery only versus 55% of the older patients ( p < 0.0001). Younger patients had improved survival at all stages. This effect was more pronounced at earlier stages (the hazard ratios for the older group were 1.84, 1.62, 1.18, and 1.14 for stages I through IV, respectively [all p < 0.0001]). The absolute differences in 5‐year overall survival between the younger and older groups were 25% for stages I and II but only 9% and 2% for stages III and IV, respectively. Conclusions: : Overall and relative survival in younger patients with NSCLC is better than in older patients, with greater benefit seen in earlier stages. Despite having fewer comorbidities and undergoing more aggressive treatment, younger patients with advanced‐stage NSCLC have only marginally better overall and relative survival than older patients.